SIMPLIFY THE FOLLOWING?

(64/125)^-2/3

ANSWER ME

PLZ

3 Answers

Relevance
  • 8 years ago

    (64/125)^-2/3

    = (4^3/5^3)^-2/3

    =((4/5)^3)^-2/3

    Since power on a power gets multiplied

    therefore

    = (4/5)^-2

    =(5/4)^2

    =25/16

    Hope it helps!!!!

    HAVE A NICE DAY!

  • 8 years ago

    (64/125)^-2/3

    =(125/64)^2/3

    =(5^/4^3)^2/3

    =(5/4)^2

    =25/16

  • 8 years ago

    (64/125)^-2/3

    = (125/64)^2/3

    = [(125^1/3)/(64^1/3)]^2

    = (5/4)^2

    = (5^2)/(4^2)

    = 25/16

Still have questions? Get your answers by asking now.